Effect of social media use on food safety risk perception through risk characteristics: Exploring a moderated mediation model among people with different levels of science literacy - Zhang, Jie; Wu, Hsi-Chen; Chen, Liang; Su, Youzhen (Frontiers in Psychology, 2022)
Food safety risk (FSR) is becoming a vital issue for public health, and improving public awareness of FSR through social media is necessary. This study aims to explore specific mechanisms of FSR perception; it first categorizes 19 risk characteristics into two variables, dread and efficacy, and then examines how social media use affects perceived FSR through both variables. Additionally, the study explores the moderating effects of source credibility and science literacy on the mechanisms of FSR perception. Based on a nationwide online survey (N = 2,015) of more than six salient food safety issues in China, the study found that exposure to food safety risk information on social media can help improve perceived FSR based on the proposed “dread–efficacy processing model” (DEPM), where dread stimulates perceived risk, while efficacy suppresses risk perception. Moreover, source credibility intensifies the effect of social media use on efficacy appraisal, whereas science literacy exerts a “double-weakening” influence on dread appraisal. Theoretical and practical implications of the findings are discussed.